Optimalisasi Pelatihan One Stop Learning (OSL) dalam Rangka Peningkatan Kompetensi Pegawai Negeri Sipil - Zulkifli, Zulkifli; Junanto, Deny; Hutrindo, Erick (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2025)
To improve organizational performance, it is necessary to have qualified employees with high levels of competence, enabling them to contribute effectively to the achievement of organizational goals. Based on this rationale, this study was conducted to examine the effect of optimizing One Stop Learning (OSL) training on employee competency at the Human Resources Development Center for Apparatus (PPSDMA), under the Ministry of Energy and Mineral Resources (ESDM). The study population comprised employees who had completed One Stop Learning training across five training programs with the highest levels of participant interest. The total population consisted of 107 individuals, from which 62 participants were randomly selected as the research sample. This study employed a mixed-methods approach, combining both quantitative and qualitative methods. The research results show that the research hypothesis is accepted, namely that Optimizing One Stop Learning Training has a significant influence on employee competency. From the qualitative perspective, several components of the OSL training program were identified as areas for potential optimization. These include: the development of training materials in terms of both content and visual presentation; increased utilization of information technology; enhancement of virtual teaching techniques; greater variation in the assignment of conceptual training tasks; enrichment of training features; the implementation of IT-based evaluation tools; and resolution of implementation-related challenges.